SIMULASI ENERGI IKAT DAN ENERGI DISINTEGRASI PELURUHAN UNSUR RADIOAKTIF DERET AKTINIUM BERDASARKAN MODEL INTI TETESAN CAIRAN (TELAAH KLASIK) - Maharani Karunia Putri; Albertus Djoko Lesmono; Alex Harijanto (Universitas Jember, 2021)
The purpose of this research is to make simulation with Matlab application to calculate the binding energy and disintegration energy of Actinium series based of liquid drop model approach. This research is experimental description. The steps: 1) prepare literature studies of elements in the radioactive process; 2) reviewing some literatures; 3) do calculation simulation; 4) analyze and discuss the results of calculations; 5) conclude the research results. The calculation results show that the binding energy value of the Actinium Series based of liquid drop model approach is in accordance with the theory where the binding energy is directly proportional to the mass and the number of particles, so that the binding energy decreases in linear graph. The largest binding energy owned by 92U235 element is 1786,751 MeV. While the smallest binding energy owned by the 81Tl20 element is 1616,311 MeV. The disintegration energy found in the radioactive actinium series has a positive value, so this is in accordance with the conditions for the occurrence of decay, which is Q> 0. The largest disintegration energy produced from alpha decay by element 91Pa231 is 4.9335 MeV and the smallest binding energy generated from beta decay by the element 90Th231 is 0,0018 MeV. Key Word: Disintegration Energy, Binding Energy, Liquid Drop Model Approach.